'I don't need you to criticise me, I need you to support me'. A qualitative study of women's experiences of and attitudes to smoking cessation during pregnancy. Issue 6 (November 2022) - Stacey, Tomasina; Samples, Jayne; Leadley, Chelsea; Akester, Lisa; Jenney, Azariah
Abstract: Background: Smoking is associated with health inequalities and is the most important modifiable risk factor for poor outcome in pregnancy. Aim: To explore women's experiences of smoking during pregnancy, examine their attitudes and barriers to smoking cessation, and to discover what support they feel might enable them to have a smoke-free pregnancy in future. Methods: A qualitative study was conducted with nineteen women in the United Kingdom who had smoked at some stage in pregnancy during the last five years. Data were collected through in-depth telephone interviews between June and August 2021. The interviews were audio-recorded, transcribed verbatim, and thematically analysed. Findings: Four key themes were identified: the complex relationship with smoking, being ready to quit, the need for support and understanding, and ideas to support a smoke free pregnancy. The findings revealed that there were two distinct avenues for enabling the support process: encouraging a readiness to quit through identifying individual context, personalised support, and educational risk perception, and, supporting the process of quitting, and offering a range of options, underpinned by a personalised, non-judgemental approach. Conclusion: Smoking in pregnancy is a complex issue resulting from a combination of social, emotional, and physical factors. The findings from this study suggest that a combination of approaches should be made available to enable pregnant women who smoke to select the best options for their individual needs. Irrespective of the practical support offered, there is a need for informed, sensitive, individualised support system that women can identify with.